The Effects of Processing Time and Temperature on the Characteristics of Candlenut Oil using the Rendering Process Method - Sulhatun; Suryati; Nurul Syawal; Nurul Fadila (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Hazelnut (Aleurits moluccana), contains nutrients and non-nutrition. Non-nutritional substances in hazelnut, for example, saponins, falvonoids, and polyphenols. In this research, the hot extraction process was carried out for candlenut raw materials, as well as product analysis for candlenut oil. The purpose of this study was to process hazelnut seeds into hazelnut oil using the rendering process method and to determine the effect of the process on the composition of the chemical compounds contained in hazelnut oil. The process parameters used were temperature and extraction process time of 65 ℃, 70 ℃ and 75 ℃ with various extraction times of 75, 100, 125 and 150 minutes. The results showed that the yield of hazelnut oil using the rendering method obtained a yield of 23.57% at an extraction time of 150 minutes and a temperature of 75℃ with a density of 0.9241 gr/ml. Analysis using Gas Chromatography Mass Spectrometry (GC-MS) in the rendering process there are five main components Margaric acid methyl ester at 8.98%, Linoleic Acid, 32.66% , Linolenic 22.31% Oleic at 33.39%. acid, Nonanoic acid of 2.66 %